On-farm reservoir systems for rainfed ricelands - IRRI (IRRI, 1994)
The book researches on the on-farm rainwater storage systems in Bangladesh, India, Indonesia and the Philippines, it determines their value in conserving rainwater, improving lan productivity, and the impact on farmer income